Seismic analysis of the Xiluodu reservoir area and insights into the geometry of seismogenic faultsKey points - Hongfu Lei; Qincai Wang; Cuiping Zhao; Ce Zhao; Jinchuan Zhang; Jun Li (Earthquake Science, 2022)
The Xiluodu (XLD) reservoir is the second largest reservoir in China and the largest in the Jinsha River basin. The occurrence of two M > 5 earthquakes after reservoir impoundment has aroused great interest among seismologists and plant operators. We comprehensively analyzed the seismicity of the XLD reservoir area using precise earthquake relocation results and focal mechanism solutions and found that the seismicity of this area was weak before impoundment. Following impoundment, earthquake activity increased significantly. The occurrence of M ≥ 3.5 earthquakes within five years of impoundment also appear to be closely related to rapid rises and falls in water level, though this correlation weakened after five years because earthquake activity was far from the reservoir area. Earthquakes in the XLD reservoir area are clustered; near the dam (Area A), small faults are intermittently distributed along the river, while Area B is composed of multiple NW-trending left-lateral strike-slip faults and a thrust fault and Area C is composed of a NW-trending left-lateral strike-slip main fault and a nearly EW-trending right-lateral strike-slip minor fault. The geometries of the deep and the shallow parts of the NW-trending fault differ. Under the action of the NW-trending background stress field, a series of NW-trending left-lateral strike-slip faults and NE-trending thrust faults in critical stress states were dislocated due to the stress caused by reservoir impoundment. The two largest earthquakes in the XLD reservoir area were tectonic earthquakes that were directly triggered by impoundment.